Changes in Children's Behavior Patterns Due to Use of Internet Media (Case Study of Elementary School Children ) Grade VI of SD Inpres 1 Toboli North Parigi District - Thio, Rikwan Mariawan; Hasdin; Rizal (Kirana Publisher (KNPub), 2025)
Development technology especially the internet world is one of needs that are not let go from life human beings . The spread of internet technology and its emergence various new type of online game make student moment This focused to a new playing arena . Formulation problem anything​​ forms change pattern behavior child consequence use of internet media, how the role of teachers and parents to internet usage in children . Research objectives For describe forms change pattern behavior child consequence use of internet media, for describe the role of teachers and parents to internet usage in children age Elementary School . Research Methods Study This including study field research with type study descriptive qualitative , namely research that seeks give description about phenomena and conditions that occur based on conditions natural object research . Research results Change behavior child that happened is a number of student during class hours No focus study and busy alone , students the perform velocity movements ( content on Tik Tok), when reprimanded by his teacher , the student he paused for a moment , and repeated it. Again when the teacher is not see to direction , besides That when the teacher explains There is cool students​ draw anime characters in books he wrote , the student who was disturbing his friend during class hours in progress like take book , take fountain pen his friend . Not only that , students become late come to school due to forgetting to play the game time . Conclusion in study Based on research that has been implemented so can withdrawn conclusion that forms change pattern behavior child consequence use of internet media can in the form of change positive and change negative .